Internalized and Perceived Stigma and Depression in Pulmonary Tuberculosis: Do They Explain the Relationship Between Drug Sensitivity Status and Adherence? - Pradhan, Anmol; Koirala, Prakash; Bhandari, Samrat Singh; Dutta, Sanjiba; García-Grau, Pau; Sampath, Harshavardhan; Sharma, Indralal (Frontiers in Psychiatry, 2022)
Background: Adherence to medication for Tuberculosis (TB) has been found to be deleteriously affected by psychosocial issues including internalized and perceived stigma (IPS) and depression usually resulting in emergence of multidrug resistant TB. The objectives of the study were to find the prevalence of depression among patients receiving treatment for Pulmonary TB and to find how stigma and depression affects the relationship between drug sensitivity status (DSS) and treatment adherence. Method: It was a cross-sectional observational study conducted between January 2019 and July 2020 in two centers in Sikkim, India. Patient Health Questionnaire-9, Internalized Social Stigma Scale, Tuberculosis Medication Adherence Scale were used to assess depression, IPS and medication adherence respectively. A path analysis was performed with DSS, treatment adherence, IPS, depression. Education in years was included in the model as it was significantly correlating with IPS. Results: 71 patients who were on drug sensitive (DS-TB) regimen (n=26) and MDR-TB regimen (n=45) participated in the study. 56.3% (n= 40) of the participants were found to have depression. Among the depressed, 32.5% were on DS-TB regimen and 67.5% were on MDR-TB regimen. The path analysis indicated that IPS and depression were serially mediating the relationship between DSS and treatment adherence (β= -0.06, p<0.05, 95% CI = -3.20, -0.02). Finally, years of education had an exogenous predictor role, not only directly affecting IPS (β = -.38, p < .001, 95% CI= -0.99, -0.31) but also affecting treatment adherence through IPS and Depression (β = .08, p = .02, 95% CI = 0.03, 0.47). This indicated that with more years of education, the IPS decreases, which decreases depression and ultimately leads to better adherence. Conclusion: We found an important relation between different psychosocial factors which may affect treatment adherence. Patients who have higher IPS are more likely to develop depression which negatively affect adherence. Patients on MDR-TB regimen have higher stigma. There is an urgent need to integrate mental health services with TB Control Programs.